Discovery of seven novel mutations of gyrB, parC and parE in Salmonella Typhi and Paratyphi strains from Jiangsu Province of China - Qian, Huimin; Cheng, Siyun; Liu, Guoye; Tan, Zhongming; Dong, Chen; Bao, Jinfeng; Hong, Jie; Jin, Dazhi; Bao, Changjun; Gu, Bing (Scientific reports, 2020)
Objective: To investigate the prevalence of Salmonella Typhi and Paratyphi resistance to quinolones and characterize the underlying mechanism in Jiangsu Province of China. Methods: Antimicrobial susceptibility testing was performed using Kirby-Bauer disc diffusion system. Quinolone resistance-determining region (QRDR), plasmid-mediated quinolone resistance (PMQR) determinant genes were detected by PCR and sequencing. Results: Out of 239 Salmonella isolates, 164 were S . Typhi and 75 were S . Paratyphi. 128 (53.6%) Salmonella isolates were resistant to nalidixic acid; 11 (4.6%) isolates to ciprofloxacin and 66 (27.6%) isolates were intermediate to ciprofloxacin. QRDR were present in 69 S . Typhi isolates, among which mutation at codon 83 ( n = 45) and 133 ( n = 61) predominated. In S . Paratyphi, the most common mutations were detected in gyrA at codon 83( n = 24) and parC : T57S ( n = 8). Seven mutations were first reported in Salmonella isolates including gyrB : S426G, parC : D79G and parE : [S498T, E543K, V560G, I444S, Y434S]. PMQR genes including qnrD1 , qnrA1 , qnrB4 , aac (6 ′ )-Ib-cr4 and qnrS1 were detected in 1, 2, 3, 7 and 9 isolates, relatively. Conclusions: High resistance to quinolones in Salmonella remains a serious problem in Jiangsu, China. The presence of the novel mutations increases the complexity of quinolone-resistant genotypes and poses a threat to public health. Subject terms: Salmonella Typhi, Salmonella Paratyphi, antimicrobial resistance, QRDR, PMQR.